China and the South China Sea : time for code of conduct? - Pablo-Baviera, Aileen San (2012)
Recent incidents in the South China Sea point to China’s growing assertiveness and seeming readiness to pressure other countries to recognise its claims. The region urgently needs a Code of Conduct that is specifically designed for the prevention of armed conflict in the disputed areas.